Implementation Guideline for Piloting Landscape- Based Fertilizer Recommendations: Engaging Scaling Partners - Legesse, Gizachew; Tigabie, Abiro; Agegnehu, Getachew; Desalegn, Henok; Desta, Gizaw (International Crops Research Institute for the Semi-Arid Tropics, 2024)
Nutrient management plays a vital role in enhancing crop yield, soil upgradation, and farmers’ profitability. Landscape-based nutrient management is an approach for estimating the nutrient requirements of crops based on landscape strata. The main principles include the identification of dynamic landscape-specific application of fertilizer considering the yield gradient along landscape positions, estimation of native nutrient supplies using a nutrient-limited yield, and estimation of nutrient requirements of a crop based on an expected yield gain. Different decision support systems (DSS) are available for various aspects of agricultural management, particularly for nutrient management.